Relationship between hypoxia and downstream pathogenic pathways in preeclampsia - Korkes, Henri Augusto; De Oliveira, Leandro [UNESP]; Sass, Nelson; Salahuddin, Saira; Karumanchi, S. Ananth; Rajakumar, Augustine (Taylor & Francis Inc, 2017)
Defects in angiogenesis and mitochondrial function in the placenta contribute to the pathogenesis of preeclampsia; however upstream regulators of these pathways are not known. It has been argued that placental hypoxia secondary to abnormal spiral artery remodeling may play a causal role in the angiogenic and mitochondrial abnormalities noted in preeclampsia. The aim of this study was to evaluate the relationship between hypoxia-inducible factor-1 (HIF-1) a surrogate of hypoxia, and soluble fms-tyrosine kinase 1 (sFlt1), a circulating anti-angiogenic factor, and microRNA 210 (miR-210), a microRNA that regulates mitochondrial function, in human placentas from preeclamptic and non-hypertensive pregnancies. We first confirmed a 2.5-fold upregulation of HIF-1 protein in placentas from preeclampsia when compared to non-hypertensive controls. Consistent with prior studies, we also observed a 10-fold upregulated sFlt1 mRNA and 2-fold upregulated miR-210 in preeclamptic tissue. Interestingly, while sFlt1 mRNA correlated with miR-210 in preeclampsia (R-2 = 0.77, p = 0.0004), there were no significant correlations between these molecules and HIF1 expression. We conclude that non-hypoxia pathways may be involved in the abnormal angiogenic and metabolic alterations noted in preeclampsia.
Keywords: HIF-1 protein; miR-210; placenta; preeclampsia; pregnancy; sFlt1